Safety of meningococcal B vaccine (4CMenB) in adolescents in Australia. Issue 37 (18th August 2020) - Marshall, H.S.; Koehler, A.P.; Wang, B.; A'Houre, M.; Gold, M.; Quinn, H.; Crawford, N.; Pratt, N.; Sullivan, T.R.; Macartney, K.
Highlights: 58, 637 doses of 4CMenB vaccine were administered to 30, 522 students. 193 AEFI including nine serious adverse events in 187 students were reported. The AEFI reporting rate was low and consistent with other adolescent vaccines. Abstract: Background: Four-component meningococcal B (4CMenB) vaccine is licensed in many countries but has had limited use in adolescents despite this age group being at increased risk of meningococcal disease. Objectives: To assess the safety profile of two doses of 4CMenB in adolescents. Methods: Cluster randomised controlled trial of senior school students in South Australia (SA) with participating schools randomised to intervention (4CMenB) or control. Vaccine safety was monitored using the South Australian Vaccine Safety Surveillance System (SAVSS), a spontaneous reporting system for adverse events following immunisation (AEFI) with enhanced follow-up of AEFI. Results: 58, 637 doses of 4CMenB vaccine were administered to 30, 522 students (median age 16 years) during 2017–2018. Of 18, 348 and 12, 174 students vaccinated in 2017 and 2018, 97.3% and 84.3%, respectively, received both scheduled doses (N = 28, 115). 193 AEFI in 187 students were reported with a reporting rate of 0.32% (95%CI: 0.28–0.39%). Seventy individuals sought medical review, including nine serious adverse events. 98% (166/169) of those who were contactable for AEFI follow-up (87.6% 169/193) reported resolution of the event. Most common AEFI were injection site reaction (126/193), headache (99/193) and nausea (61/193). AEFI were more frequently reported in females (aOR = 1.409 (95%CI: 1.002, 1.980)), schools with high level of educational advantage (adjusted Odds Ratio (aOR) = 1.515 (95%CI: 1.005, 2.284)), following first dose (aOR = 1.619 (95%CI: 1.168, 2.244)), and in 2017 (aOR = 1.437 (95%CI: 1.001, 2.064)). Reported AEFI declined with increasing age (aOR = 0.771 (95%CI: 0.673, 0.883)). Conclusion: In this largest post-licensure use of 4CMenB in adolescents, the low AEFI reporting rate provides real-world evidence of 4CMenB safety in this age group. (ClinicalTrials.gov number: NCT03089086).